Success rate of radioactive iodine treatment for children and adolescent with hyperthyroidism - S. Namwongprom (2020)
© 2020, Italian Society of Endocrinology (SIE). Purpose: To assess the success rate of first dose radioiodine for treatment of hyperthyroidism in children and adolescent. Methods: This is a retrospective data analysis of children and adolescent with hyperthyroidism who received radioiodine (RAI) therapy from January 2013 to December 2017. Age, gender, family history of hyperthyroidism, duration of anti-thyriod drugs (ATDs) treatment, rapid turnover status, 2 h and 24 h I-131 radioiodine uptake (RAIU), thyroid volume, and treatment dose were also analyzed. The goal of RAI therapy was to achieve hypothyroidism within 3–6 months after treatment. Treatment result was evaluated at 6 months after treatment and divided into 2 groups: treatment success (hypothyroid and euthyroid) and treatment failure (hyperthyroid). The same parameters were compared between both groups. Results: 32 hyperthyroid patients, 26 female with mean age at treatment of 13.84 ± 1.83 years. All patients had prior treatment with ATDs, with a median treatment duration of 32.5 months (range 2–108). The median estimated thyroid gland size was 24.62 g, range 9.29–72.8. RAI doses ranged from 4.1 to 29.9 mCi (median dose = 7.54 mCi). Significant difference in 24-h I-131 uptake and RI status was demonstrated. Successful treatment rate after single dose of therapeutic I-131 was 65.63%. Conclusion: With the I-131 dose of 220 μCi/g of thyroid tissue, successful treatment rate after single dose of therapeutic I-131 was 65.63%. RAI therapy with I-131 dose of 250–400 μCi/g of thyroid tissue might be suitable in patients with medical failure from ATDs. Possible role of RI as the predictor for RAI therapy failure are needed to investigate in both adult and children clinical settings.